Dyadic judgments based on conflicting samples: the failure to ignore invalid input - Fiedler, Klaus; Krüger, Tobias; Koch, Alex; Kutzner, Florian (Journal of behavioral decision making, 2020)
The present research demonstrates a so far unrecognized impediment of group performance, metacognitive myopia (Fiedler, 2012). Judges and decision-makers follow the given samples of information uncritically and neglect the metacognitive assessment of the samples' validity. Applying this notion to dyadic judgments, we instructed dyads to jointly estimate conditional probabilities p (Win|A) and p (Win|B) of Lotteries A and B. One person per dyad experienced a valid sample (winning rates conditional on lotteries). The other person experienced an invalid, reverse sample (lotteries conditional on winning). Whereas valid samples provide unbiased estimates of lotteries' winning probabilities, invalid samples can greatly misrepresent the association of winning and lotteries (depending on lottery base rates). Across three experiments, metacognitive myopia—both at the individual and at the dyadic group level—prevented participants from discriminating valid and invalid samples. Group judgments were biased toward erroneous implications of invalid samples, reflecting an equality bias among unequal group members.